SCANNING ELECTRON MICROSCOPIC STUDIES ON DEVELOPMENT OF LABEO ROHITA (HAM.) WITH REFERENCE TO INDUCED BREEDING AT MID-ALTITUDINAL REGION, SHILLONG (MEGHALAYA) - Sarma, D; Dutta, A (Journal of the Inland Fisheries Society of India, 2016)
Labeo rohita (Ham.) was successfully induced to breed at mid altitudinal region, Shillong, at a temperature of 19-23oC. The surface microstructure of eggs and hatchlings were observed. The smaller size and rough surface architecture of theeggs and hatchling denotes incomplete development. The surface ultrastructure, cellular morphology, differences in cell shape and the type of cell were observed through SEM.Unlike other teleosts some characteristic features like uniformdistribution of filopodia throughout the embryonic shield, smaller diameter of filopodia and extension of embryonic axis were seen.